PERKEMBANGAN EMOSI DAN PERKEMBANGAN BAHASA PADA REMAJA: PERKEMBANGAN EMOSI DAN PERKEMBANGAN BAHASA PADA REMAJA - Sartika Akarama; Zihan Usman; Abd Rahman K. Ma'ruf (Jurnal Ilmu Pendidikan dan Budaya, 2023)
This study discusses emotional development and language development in adolescents. Emotional and language development in adolescents are two important aspects in this challenging phase of life. Teenagers experience major physical, cognitive and social changes that affect the way they think, feel and interact with the world around them. At this stage, emotion and language serve as the main tools for adolescents to understand themselves, express themselves, and build relationships with others. Emotional and language development in adolescents are interconnected and influence each other. Language plays an important role in the expression of emotions. With words, youth can describe their feelings to others, seek support, or explain what they are experiencing. Conversely, the emotions experienced by adolescents can also affect their ability to use language. When strong emotions are felt, it can be difficult for teens to express themselves clearly and logically. Therefore, it is important for adolescents, parents and educators to understand and support emotional and language development in adolescents. By providing a safe and supportive environment and opportunities to practice speaking and listening, we can help youth develop healthy and effective emotional and language skills. In this way, adolescents can learn to manage their emotions well, communicate effectively, and build meaningful relationships with others during this important transition. This study uses a qualitative research method that aims to explain a phenomenon in depth and is carried out by collecting data as deeply as possible. Qualitative methods prioritize the observation of phenomena and examine more the substance of the meaning of these phenomena. This study was also structured to fulfill assignments for development and recognition of student characteristics courses. In addition, this study identified factors that influence emotional development including the family environment, peer environment, school environment, community environment and social media. Factors of language development in adolescents, including biological factors, family environment, social interaction, education, cognitive factors, and cultural factors. A language-rich family environment, extensive social interaction, quality education, and supportive cultural factors have a positive impact on adolescent language development. In this context, it is important for adolescents, parents and educators to support emotional and language development in adolescents. Creating a safe and supportive environment, as well as providing opportunities to practice speaking and listening, can help youth develop emotional skills